The Validity of Authentic Islamic Value-Based Assessment Instruments in Contemporary PAI Education: A Conceptual Analysis - Sari, Emilda Yuli Puspita; Shohib, Muhammad Wildan; Anshori, Ari (Universitas Muhammadiyah Surakarta, 2025)
Purpose: This study aims to conceptually analyze the validity of authentic assessment instruments based on Islamic values in the context of the evaluation of Islamic Religious Education (PAI) learning in the contemporary era. Methodology: This study adopted a library research approach with a conceptual–descriptive design to construct a theoretical understanding of Islamic validity in authentic assessment. Data sources consisted of primary Islamic classical texts and secondary contemporary literature on validity, authentic assessment, and Islamic education, selected from peer-reviewed publications indexed in Scopus, Google Scholar, and DOAJ (2019–2025). The analysis involved systematic identification, screening, thematic categorization, and synthesis of the literature to integrate modern validity theory with the Islamic values of sidq, ‘adl, and amanah. The study applied theoretical triangulation to ensure credibility, resulting in an integrative conceptual model that links empirical, interpretive, and ethical spiritual dimensions of assessment validity. Results: The results of the study show that validity in PAI must be understood as a unity between scientific validity and moral validity based on the values of sidq (honesty), 'adl (justice), and amanah (responsibility). The integration of Islamic values in assessment instruments can be carried out through three approaches, namely epistemological (intention to seek truth), methodological (justice in procedures), and axiological (use of results for the benefit). Applications/Originality/Value: This study proposes an original three-dimensional Islamic Validity model—empirical, interpretive, and spiritual—that extends contemporary validity theory by integrating Islamic ethical values. The model can be applied in designing authentic and ethically responsible digital assessments in PAI. By addressing ethical challenges in assessment digitization and strengthening students’ character, this research contributes to a scientifically valid, socially just, and spiritually meaningful evaluation paradigm aligned with 21st-century learning.